Pulmonary artery sarcoma treated with pulmonary endarterectomy and leaflet reconstruction using Ozaki technique - AK, KORAY; ÖZTÜRK, FATİH; BOZKURTLAR, EMİNE; ARSAN, SİNAN; YILDIZELİ, BEDRETTİN (My University, 2022)
Pulmonary arterial intimal sarcomas (PAIS) are rare malignancies with a poor prognosis. Sarcomas present with signs and symptoms mimicking pulmonary thromboembolic disease, delaying the diagnosis. We present a 29-year-old male patient diagnosed with PAIS in the right and main pulmonary arteries extending to the left pulmonary leaflet. The patient was treated with pulmonary endarterectomy and pulmonary leaflet reconstruction using the Ozaki technique.
Keywords: Tıp; Dahili Tıp Bilimleri; Kardiyoloji; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Cardiovascular; Surgery Medicine Sciences; Health Sciences; KALP VE KALP DAMAR SİSTEMLERİ; Klinik Tıp; Klinik Tıp (MED); CERRAHİ; CARDIAC & CARDIOVASCULAR SYSTEMS; CLINICAL MEDICINE; Clinical Medicine (MED); SURGERY; Cerrahi; Kardiyoloji ve Kardiyovasküler Tıp; Surgery; Cardiology and Cardiovascular Medicine; aorta and great vessels; cardiovascular pathology; valve repair; replacement; FEATURES; aorta and great vessels; cardiovascular pathology; valve repair/replacemen